THE INFLUENCE OF STRATEGIC PLANNING AND MARKET EXPANSION ON COMPANY PERFORMANCE PT. MENTARI MEGA MAKMUR LAMPUNG - Mei Liana Fransiska; Habiburrahman (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine the effect of strategic planning and market expansion on the performance of PT. Mentari Mega Makmur Lampung. A quantitative approach was used as the research method. The population of the study consists of all employees and stakeholders involved in the research topic, totaling 30 respondents. The data used included both primary and secondary data. Data collection was conducted through interviews using a 5-point Likert scale-based questionnaire. Multiple linear regression analysis was performed using SPSS version 25 to support the research. The results showed that strategic planning has a positive but insignificant effect on company performance. Conversely, market expansion has a positive and significant effect on company performance. Simultaneously, strategic planning and market expansion demonstrate a significant influence on company performance.